Análisis del encadenamiento entre actividades productivas en la economía Boliviana - Paul S. Bustos Anaya (Universidad Católica Boliviana, Instituto de Investigaciones Socio-Económicas (IISEC), 2011)
– This paper explores the relation between activities in the Bolivian economy as suppliers and demanders of intermediate inputs, this whit the purpose to determine which activities have great impact on the rest of the economy and which ones are less integrated. For this, Rasmussen indexes are used, that allow classifying them as independent, push, pull and key activities; this whit the help of the input-output matrix. The results based on 2008 data, show a little integrated economy, which is divided in 35 activities. There are no key activities, 8 activities are considered strategic and only trade is considered a pull sector. Something outstanding about the results is that trade generates great dynamism in the rest of activities through its indirect effects on transportation more than because of its direct demand of inputs.
Keywords: C1; D2; L1; 330; Índices de Rasmussen; actividad clave; actividad estratégica; actividad de arrastre; actividad independiente; poder de dispersión; sensibilidad de dispersión; matriz insumo producto; Input-Output; Bolivien